Dual Sourcing and Smoothing Under Nonstationary Demand Time Series: Reshoring with SpeedFactories - Boute, Robert N.; Disney, Stephen M.; Gijsbrechts, Joren; Van Mieghem, Jan A. (Management Science, 2022)
We investigate near-shoring a small part of the global production to local SpeedFactories that serve only the variable demand. The short lead time of the responsive SpeedFactory reduces the risk of making large volumes in advance, yet it does not involve a complete reshoring of demand. Using a break-even analysis, we investigate the lead time, demand, and cost characteristics that make dual sourcing with a SpeedFactory desirable compared with complete off-shoring. Our analysis uses a linear generalization of the celebrated order-up-to inventory policy to settings where capacity costs exist. The policy allows for order smoothing to reduce capacity costs and performs well relative to the (unknown) optimal policy. We highlight the significant impact of auto-correlated and nonstationary demand series, which are prevalent in practice yet challenging to analyze, on the economic benefit of reshoring. Methodologically, we adopt a linear policy and normally distributed demand and use Z–transforms to present exact analyses. This paper was accepted by Jayashankar Swaminathan, operations management.